Analisis Penerapan Asesmen Autentik dalam Mengukur Prestasi Atletik di SD - Nadila Nurfauziah; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the application of authentic assessment in measuring the athletic achievement of elementary school students. The study used a descriptive qualitative approach implemented in three elementary schools, with research subjects including principals, Physical Education teachers, and athletic students. Data collection techniques were carried out through observation, semi-structured interviews, and documentation, while data analysis used an interactive model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that authentic assessment has been implemented in athletic learning through performance-based assessment, process observation, and providing feedback on running, jumping, and throwing activities, but the level of consistency and depth of implementation varies between schools and teachers. Authentic assessment is able to provide a more objective and contextual picture of student athletic achievement, although its implementation still faces obstacles such as limited teacher competence, minimal ongoing training, and uneven school support. The conclusion of this study shows that authentic assessment has the potential to be an effective evaluation instrument in measuring the athletic achievement of elementary school students if supported by increased teacher capacity, applicable assessment guidelines, and school policies that support consistent implementation. Keywords: Athletic Achievement, Authentic Assessment, Elementary School, Learning Evaluation, , Physical Education.